2014
DOI: 10.1071/ch14032
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on Phosphorescent Materials: The Conjugation-Extended PtII Complexes

Abstract: A theoretical study on the Pt II complex A based on a dimesitylboron (BMes 2 )-functionalized [Pt(C^N)(acac)] (C^N ¼ 2phenyl-pyridyl, acac ¼ acetylaceton) complex, as well as three conjugation-extended analogues of the methylimidazole (C*) ligand BMes 2 -[Pt(C^C*)(acac)] complexes B-D is performed. Their theoretical geometries, electronic structures, emission properties, and the radiative decay rate constants (k r ) were also investigated. The energy differences between the two highest occupied orbitals with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Besides, previous studies have shown that the SOC between the lowest triple excited state and the ground state is another temperatureindependent factor affecting the non-radiative rate constant. [54][55][56][57] The stronger the SOC effect is, the more easily the excited state will return to the ground state in the form of intersystem transition, causing the phosphorescence quenching. According to Table 7, the value of SOC between the lowest triple excited state and the ground state of Pt-C10 is 94.52 cm À1 , which is smaller than that of Pt-C11 (100.37 cm À1 ) and has a smaller Huang-Rhys factor.…”
Section: Temperature-independent Nonradiative Rate Constantsmentioning
confidence: 99%
“…Besides, previous studies have shown that the SOC between the lowest triple excited state and the ground state is another temperatureindependent factor affecting the non-radiative rate constant. [54][55][56][57] The stronger the SOC effect is, the more easily the excited state will return to the ground state in the form of intersystem transition, causing the phosphorescence quenching. According to Table 7, the value of SOC between the lowest triple excited state and the ground state of Pt-C10 is 94.52 cm À1 , which is smaller than that of Pt-C11 (100.37 cm À1 ) and has a smaller Huang-Rhys factor.…”
Section: Temperature-independent Nonradiative Rate Constantsmentioning
confidence: 99%
“…They are heavy metal atoms that can induce strong spin-orbit coupling (SOC) and promote an effective intersystem crossing (ISC), which results in higher quantum efficiency. [7][8][9][10][11] Platinum which has the second largest SOC constant, tends to form planar structure due to the d 8 electron conguration of the Pt(II) ion. The ligand of cyclometalated Pt(II) complexes can be designed as bidentate, tridentate and tetradentate.…”
Section: Introductionmentioning
confidence: 99%
“…Among heavy metal complexes, Ir(III) complexes excel in inducing strong spin-orbit coupling (SOC), promoting efficient inter-system crossover (ISC), and achieving heightened quantum efficiency. SOC can be boosted by introducing heavy atoms or altering electronic configurations from single to triplet states [15][16][17][18][19]. In summary, leveraging the effectiveness of (mdp) 2 Ir(acac)-where mdp represents 4-methyl-2,5-diphenylpyridine and acac stands for acetylacetone-as demonstrated by density functional theory (DFT) and time-dependent density functional theory (TD-DFT), we adopted it as a reference to systematically devise a series of Ir(III) complexes [20].…”
mentioning
confidence: 99%